Development of Pec Based Electrical Load Schedule Software - Alvaro, Ralph G.; B. Cabrera, Eric Kenneth; G. Gutierrez, Raineir Ryan; D. Punzalan, Joshua; G. Serrano, Louie; L. Tangcuangco, Alma (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
This paper presents the development of PEC-based electrical load schedule software for residential electrical services design. All the sources that will be used for the computation and data will be based on PEC. The testing of the project will be carried out in accordance with PEC as well as other approved codes. Calculating tools to help you understand the process of accurately sizing a commercial electrical panel based on proposed loads. To emphasize, accurate load sizing is best performed by an electrical engineer, which is reviewed by the building department in your jurisdiction. The software was developed using Visual Basic (VB. net) programming language. Vb.net, or Visual Basic, is a development of the BASIC programming language. It is intended to be used in conjunction with an Integrated Development Environment (IDE). Prior to the development of IDEs, programming languages like BASIC relied significantly on the DOS command-line. A load schedule for different operating scenarios will show when peak consumption occurs and provide an opportunity to find out if all the high loads must operate at this time. It serves as a valuable calculation tool for electrical engineers, students, and technicians by providing a faster, easier, and more accurate means of carrying out some basic calculations, such as determination of the size of wire; conduit sizes; circuit breaker ratings; the main feeder size of wires; main circuit breaker ratings; voltage drop; and riser diagram using Philippine Electrical Code Tables. The results of these calculations help the designer to make vital decisions such as cable sizing and nominal ratings of protective devices required by each circuit and by the entire installation, in line with appropriate standards and regulations.